Smoking and bladder cancer: insights into pathogenesis and public health implications from a bibliometric analysis (1999–2023) - Yang Wang; Hancheng Zhou; Zhicheng Tang; Zhaohui He; Hui Zhuo; Yi Huang; Jianqiu Kong (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background Cigarette smoking is a major contributor to the global burden of bladder cancer. Its carcinogenic effects result from the harmful substances in tobacco smoke, which induce genetic mutations and disrupt cellular processes. Understanding how smoking contributes to bladder cancer is essential for developing effective prevention and treatment strategies. Objective This study systematically reviews global research on the relationship between smoking and bladder cancer through bibliometric analysis, identifying research hotspots, trends and future directions. Methods Relevant literature on the relationship between cigarette smoking and bladder cancer published between 1999 and 2023 was retrieved from the Web of Science database. Visual analyses were conducted using VOSviewer and CiteSpace software, focusing on contributions from countries, institutions, journals, authors and keywords. Results Our analysis of 2,802 publications revealed an upward trend in annual output on the relationship between smoking and bladder cancer, with the United States and China as leading contributors. Notable institutions included the NIH, National Cancer Institute, University of Texas System and the International Agency for Research on Cancer. Key journals were Cancer Epidemiology, Biomarkers & Prevention and International Journal of Cancer. Rothman, Nathaniel and Zeegers, M.P.A. were the most productive and co-cited authors. Keyword analysis highlighted DNA repair, genome-wide association studies, and smoking cessation. Conclusion This bibliometric analysis has significantly advanced the field by highlighting current research directions and the application of specific mechanisms. These findings also have implications for clinical practice and public health policy, potentially improving patient outcomes through a comprehensive understanding of disease pathogenesis.